2002
DOI: 10.1110/ps.31702
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and nonconserved features of the folding pathway of hisactophilin, a β‐trefoil protein

Abstract: Based on previous studies of interleukin-1␤ (IL-1␤) and both acidic and basic fibroblast growth factors (FGFs), it has been suggested that the folding of ␤-trefoil proteins is intrinsically slow and may occur via the formation of essential intermediates. Using optical and NMR-detected quenched-flow hydrogen/deuterium exchange methods, we have measured the folding kinetics of hisactophilin, another ␤-trefoil protein that has <10% sequence identity and unrelated function to IL-1␤ and FGFs. We find that hisactoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 50 publications
4
22
1
Order By: Relevance
“…The modeling is consistent with experimentally observed large decreases in hisactophilin folding rate with decreasing pH (19,24).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The modeling is consistent with experimentally observed large decreases in hisactophilin folding rate with decreasing pH (19,24).…”
Section: Resultssupporting
confidence: 88%
“…For hisactophilin, we observed two-state folding with a relatively high energy barrier (5.9 kT) (Fig. 1C) consistent with experimentally observed relatively slow folding (24). While the native topology-based model captures many features of the folding energy landscape, it neglects the roughness of the landscape due to nonnative interactions, which surely exist to some extent.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…As highlighted by Meiering and coworkers, 47 the folding of FGF-1 was thought to differ from the folding pathways of both hisactophilin and IL-1b. The basis for this conclusion was a report that probed the folding of FGF-1 using NMR H/D exchange studies and identified the association of the N-and C-termini as the first step in the folding pathway.…”
Section: Discussionmentioning
confidence: 98%
“…51 Thus, our analysis of the folding of FGF-1 is inconsistent with the published report of Yu and coworkers, 48 but is in general agreement with the folding studies of other b-trefoil proteins in which the central strands of the protein are observed to fold faster than those on the periphery. 47,52,53 Only a key subset of structural elements (turns #2-#5 and turn #7, spanning $50% of the overall protein) appears necessary to confer efficient foldability to FGF-1. The entire protein is not (and apparently does not need to be) optimized for foldability; the regions not contributing to formation of the folding transition state instead segregate to regions of HSPG and receptor-binding functionalities.…”
Section: Discussionmentioning
confidence: 99%